RASIO DAN KOMPETENSI DOSEN PAI UNIVERSITAS SEBELAS MARET SURAKARTA - Muh. Muchtarom (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Regarding to the reality of Islamic Religious Education (or PAI) lecturer at UNS, that the ratio between the number of PAI lecturers with the number of the students is incomparable, the number of credits for PAI is 2 credits in the general population, the implementation of the PAI study is in odd and even semesters, UNS PAI lecturers are civil servants appointed by the Education Ministry. Furthermore the teachers competence Islamic Education which includes the competence of personality, pedagogic, professional, social, and religious competence had met a good competence. Key Words: Lecturer, Ratio, and Competence.